Synthesis and characterization of photo-crosslinkable 4-styryl-pyridine modified alginate. (10th July 2016) - Elsayed, Nadia H.; Monier, M.; Alatawi, Raedah A.S.
Highlights: Sodium alginate (SA) was modified by insertion of 4-styryl-pyridine moieties. The resulted polymer was characterized by various instrumental methods. Photo-induced crosslinking was performed by UV irradiation. The morphology, swelling and mechanical properties were examined. Abstract: In this article photo-crosslinkablestyryl-pyridine modified alginate (ASP-Alg) was prepared and entirely investigated utilizing different instrumental techniques such as Elemental analysis, Fourier transform infrared (FTIR), 13 C and 1 H nuclear magnetic resonance (NMR), ultraviolet-visible light (UV-vis), X-ray diffraction (XRD) spectra and scanning electron microscope (SEM). Upon irradiation in the UV region, the casted ASP-Alg membranes were cross-linked through the [2π + 2π] cycloaddition reaction of the inserted photo-active styryl pyridine moieties. Both cross-linking density and kinetics were monitored by examining the UV–vis light spectra of the irradiated membrane at predetermined time intervals and the obtained results were found to fit with the second order mathematical kinetic model, revealing the performance of the cross-linking via bimolecular [2π + 2π] cycloaddition reaction. Also, the swelling behaviors along with biodegradability were also studied, and the results indicated the decrease of the swelling ratio and degradation rate by increasing the cross-linking density. Moreover, the mechanical properties were also examined under both wet and dry conditions.